Nitrogen and phosphorus fertilization promotes rapid initial growth of leucaena on Alfisol - Cobbina, J. (Informa UK Limited, 1991)
Determines whether small quantity of nitrogen fertilizer in combination with phosphorus will enhance rapid early growth of Leucaena leucocephala, especially, on the highly weathered, low organic matter and low available P soils; and concludes that fertilizer N and P application increased growth rates sharply thus hastening shoot and root dry matter accumulation.